2011
DOI: 10.1016/j.febslet.2011.03.064
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and effector T cell subsets causing autoimmune CNS disease

Abstract: a b s t r a c tAlthough experimental autoimmune encephalomyelitis (EAE) is limited in its potency to reproduce the entirety of clinical and histopathologic features of multiple sclerosis (MS), this model has been successfully used to prove that MS like autoimmunity in the CNS is orchestrated by autoantigen specific T cells. EAE was also very useful to refute the idea that IFN-c producing T helper type 1 (Th1) cells were the sole players within the pathogenic T cell response. Rather, ''new'' T cell lineages suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 227 publications
1
91
0
2
Order By: Relevance
“…Of major interest in this study is the suppressed release of T cell effector cytokines: IFN-g and IL-17. These cytokines represent the markers of Th1 and Th17 cells, which have been considered the major driving force of inflammation and autoimmunity in MS (24). EP and DMF provoked a drop in macrophage release/ production of cytokines (IL-6 and TNF) and reactive species (NO and ROS), which promote neuroinflammatory and neurodegenerative events in MS. For example, it has been shown that IL-6 potentiates the resistance of effector T cells to regulatory T cells in MS (34), and that soluble TNF actively contributes to demyelination and axonal degeneration in EAE neuroinflammation (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of major interest in this study is the suppressed release of T cell effector cytokines: IFN-g and IL-17. These cytokines represent the markers of Th1 and Th17 cells, which have been considered the major driving force of inflammation and autoimmunity in MS (24). EP and DMF provoked a drop in macrophage release/ production of cytokines (IL-6 and TNF) and reactive species (NO and ROS), which promote neuroinflammatory and neurodegenerative events in MS. For example, it has been shown that IL-6 potentiates the resistance of effector T cells to regulatory T cells in MS (34), and that soluble TNF actively contributes to demyelination and axonal degeneration in EAE neuroinflammation (35).…”
Section: Discussionmentioning
confidence: 99%
“…This model has been proved useful in studying pathological mechanisms of MS. Also, some of the MS therapies, including Copaxone and natalizumab, emerged from EAE studies (23). Th phenotypes that produce IFN-g or IL-17, that is, Th1 and Th17 cells, are considered to be the major pathogenic population in MS and EAE (24). Their interactions with APCs, such as dendritic cells and macrophages, both within the CNS and in lymphoid organs, are essential for initiation and propagation of autoimmune response directed against the CNS (25).…”
mentioning
confidence: 99%
“…MS is thought to occur in genetically predisposed individuals under certain environmental conditions, leading to the development of CNS Agspecific Th1 and Th17 cells (2), which can then be reactivated by their cognate Ag in the CNS and cause autoimmune disease (3). This development of CNS autoimmunity can be modeled in susceptible mouse strains by immunizing them with CNS Ags, for example, myelin peptides, resulting in myelin-specific Th1 and Th17 responses and experimental autoimmune encephalomyelitis (EAE) (4).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…At day 15 p.i., IFN-γ, TNF, GM-CSF, IL-27, and iNOS but not IL17 mRNA was increased in GFAP-Cre FasL fl/fl mice as compared with that in FasL fl/fl mice. IFN-γ, TNF, and GM-CSF have been reported to contribute to disease progression and demyelination in EAE [7,28]. GM-CSF and IFN-γ are mainly produced by encephalitogenic T cells.…”
Section: Discussionmentioning
confidence: 99%